2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854454
|View full text |Cite
|
Sign up to set email alerts
|

A maximal figure-of-merit learning approach to maximizing mean average precision with deep neural network based classifiers

Abstract: We propose a maximal figure-of-merit (MFoM) learning framework to directly maximize mean average precision (MAP) which is a key performance metric in many multi-class classification tasks. Conventional classifiers based on support vector machines cannot be easily adopted to optimize the MAP metric. On the other hand, classifiers based on deep neural networks (DNNs) have recently been shown to deliver a great discrimination capability in automatic speech recognition and image classification as well. However, DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 22 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…In addition, compared with that of YOLOv3-53, the loss function value of YOLOv3-13 has more and bigger fluctuations. As performance evaluation indicators, Intersection Over Union (IoU) and mAP are commonly used in target detection [36]. The IoU is often used for edge frame overlap or positioning accuracy evaluation.…”
Section: Model Training and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared with that of YOLOv3-53, the loss function value of YOLOv3-13 has more and bigger fluctuations. As performance evaluation indicators, Intersection Over Union (IoU) and mAP are commonly used in target detection [36]. The IoU is often used for edge frame overlap or positioning accuracy evaluation.…”
Section: Model Training and Evaluationmentioning
confidence: 99%
“…During the experiment, through accuracy evaluation for two-category target detection, the mean accuracy AP was calculated first of all, and then the mAP value was obtained. As performance evaluation indicators, Intersection Over Union (IoU) and mAP are commonly used in target detection [36]. The IoU is often used for edge frame overlap or positioning accuracy evaluation.…”
Section: Model Training and Evaluationmentioning
confidence: 99%
“…It was shown that discriminative learning outperforms a binary classification manner in automatic speech recognition and applied in minimum error classification [28] and minimum verification error [29]. The second approach explores the maximal figure-of-merit (MFoM) [30], [31] learning solution, which allows us to approximate the metrics of interest, namely the micro-F1 and equal error rate (EER), with a differentiable function, so that gradient-based optimization algorithms can be applied to learn DNN parameters. Specifically, MFoM tries to improve the decision boundary [30] using the output sigmoid scores without the need of any intermediate calibration.…”
Section: Motivationmentioning
confidence: 99%
“…where R denotes the number of images in a testing set, and Ra denotes the number of images that are correctly classified. Mean average precision (mAP) [33] is also used to measure the effectiveness of our method in multiclass classification.…”
Section: Weakly Supervised Localizationmentioning
confidence: 99%